Brain activity during saliva swallowing on functional magnetic resonance imaging - HIRATSUKA, Munehisa; KISE, Norimoto; MATAYOSHI, Sen; SUZUKI, Mikio; KIYUNA, Asanori (jibi to rinsho, 2016)
Upper (cerebrum cortex) and lower (mainly the medulla oblongata) brain region neural mechanisms related to swallowing have been identified. Although a number of studies have clarified the functional anatomy of swallowing in the lower region, the details regarding the control of swallowing in the upper region are still poorly understood. In recent years, several objective and minimally invasive techniques for measuring the brain activity have been developed, such as functional magnetic resonance imaging (fMRI). In the present study, we investigated the areas of brain activation associated with neural activity during saliva swallowing in six healthy subjects using fMRI. We used an event-related design for the study. The sensorimotor cortex, premotor cortex, supplementary motor, basal ganglia, thalamus, anterior cingulate gyrus, insula, and cerebellum all showed activation. Given that these extensive neural networks are involved with each other, we concluded that the upper central region of the brain controlled complex swallowing movements. Studies using noninvasive brain imaging techniques such as fMRI may clarify the connections between these swallowing neural mechanism networks. As such, more fMRI studies should be conducted in the future.